Blood-Brain Barrier Integrity and Glial Support: Mechanisms that can be targeted for Novel Therapeutic Approaches in Stroke - Ronaldson, Patrick T. (2012)
The blood-brain barrier (BBB) is a critical regulator of CNS homeostasis. Additionally, the BBB is the most significant obstacle to effective CNS drug delivery. It possesses specific charcteristics (i.e., tight junction protein complexes, influx and efflux transporters) that control permeation of circulating solutes including therapeutic agents. In order to form this “barrier,” brain microvascular endothelial cells require support of adjacent astrocytes and microglia. This intricate relationship also occurs between endothelial cells and other cell types and structures of the CNS (i.e., pericytes, neurons, extracellular matrix), which implies existence of a “neurovascular unit.” Ischemic stroke can disrupt the neurovascular unit at both the structural and functional level, which leads to an increase in leak across the BBB. Recent studies have identified several pathophysiological mechanisms (i.e., oxidative stress, activation of cytokine-mediated intracellular signaling systems) that mediate changes in the neurovascular unit during ischemic stroke. This review summarizes current knowledge in this area and emphasizes pathways (i.e., oxidative stress, cytokine-mediated intracellular signaling, glial-expressed receptors/targets) that can be manipulated pharmacologically for i) preservation of BBB and glial integrity during ischemic stroke and ii) control of drug permeation and/or transport across the BBB in an effort to identify novel targets for optimization of CNS delivery of therapeutics in the setting of ischemic stroke.